Efectos de dos sistemas de labranza sobre poblaciones de arroz rojo (Oryza sativa L.) en un agroecosistema arrocero inundado. - Ortega, Yemel M. (2005)
Effects of two tillage systems on red rice (Oryza sativa L.) populations in a flooded rice agroecosystem. The influence of two tillage systems was evaluated on red rice (Oryza sativa L.) populations and other frequent weeds in rice agroecosystems throughout four consecutive cycles of commercial flooded rice. In order to estimate the seed bank size, soil samples from three depths (0 to 5, 5 to 20 and 20 to 40 cm) were taken at the beginning of each crop cycle. The density of the most abundant weeds in the crop area was also measured. In both tillage systems there were significant differences in emerged weeds and seed banks. While the red rice seed bank and its emerged populations on the field presented incremental trends in conventional mechanized sowing (CMS), a progressive decrease in bank size and a lower density was observed in direct seeding into stubble (DSS), during cycles in which no tillage was used. Populations of annual sedges like Cyperus spp. and Fimbristylis milliaceae increased in both tillage systems, with greater intensity in CMS. The vertical distribution of the weed seed bank in the soil was also different for both tillage systems. In DSS more than 66% of the red rice seed bank and 82% of the germinated seeds were found within the first five cm of the soil profile. It is concluded that the DDS system promotes favorable conditions to maintain control over red rice populations and other weeds in flooded rice.